2005
DOI: 10.1111/j.1525-1470.2005.22216.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy and Safety of the 308 nm Excimer Laser for the Treatment of Localized Psoriasis in Adults and in Children: A Pilot Study

Abstract: The 308-nm excimer laser has been shown to be safe and efficacious in the treatment of localized mild-to-moderate plaque-type psoriasis in adults. However, the laser's safety and efficacy has not yet been demonstrated in children. Four of seven children with a mean age of 11.0 years and 12 of 18 adults with a mean age of 48.8 years completed the full protocol. The most common reason for incompletion was noncompliance unrelated to side effects. Both the children (p=0.0200) and the adult groups (p=0.0009) yielde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…A pilot study has reported 308 nm excimer laser to be a safe and effective treatment for localized psoriasis in children as in adults. [64] CONCLUSION Childhood psoriasis represents a special challenge to dermatologists. Limited data suggests that psoriasis in Indian children differs from western countries in having a later onset, equal sex distribution, infrequent facial involvement, low frequency of guttate lesions, more frequent involvement of the soles, and a low incidence of familial occurrence.…”
Section: Phototherapymentioning
confidence: 98%
“…A pilot study has reported 308 nm excimer laser to be a safe and effective treatment for localized psoriasis in children as in adults. [64] CONCLUSION Childhood psoriasis represents a special challenge to dermatologists. Limited data suggests that psoriasis in Indian children differs from western countries in having a later onset, equal sex distribution, infrequent facial involvement, low frequency of guttate lesions, more frequent involvement of the soles, and a low incidence of familial occurrence.…”
Section: Phototherapymentioning
confidence: 98%
“…Pahlajani et al compared the efficacy and safety of a 308-nm excimer laser in children and adults [35]. Both the children (4 patients with a mean age of 11 years) and adults (12 patients with a mean age of 49 years) showed a significant decrease in PASI score.…”
Section: Childhood Psoriasismentioning
confidence: 97%
“…Some data on usage in childhood shows benefi t for children with localized psoriasis, and children may experience superior benefi t with excimer usage. Therapy has some ultraviolet light induced side effects, but is generally well tolerated [ 98 ].…”
Section: Phototherapymentioning
confidence: 99%